Optimal Height And Location Model (OHALM) for rainwater harvesting small dams (Iraqi western desert- case study) - ., Rasha Ismaeel Naif; ., Isam M. Abdulhameed (Iraqi Journal of Civil Engineering, 2022)
Dams are considered as the best solution to conserve water especially in arid and semi-arid regions. This study aims to design a small dams series to conserve rainfall water. Mathematical model is proposed to optimize these dams height and locations, its named as Optimal Height And Location Model (OHALM). In this study, new method is introduced to estimate the optimal water level and volume of storage by combining between the digital elevation model generated by the Advanced Space borne Thermal Emission and Reflection Radiometer (ASTER) data, and the proposed model (OHALM). Two dams sites were selected for checking the validity of proposed method. The results of the present study showed that the error percentage increase or decrease from reference value by 3.5%, 13% for water level in Al-Rutba dam and Horan 3 dam respectively, and by 6.63%, 35.8% from volume of storage in Al-Rutba dam and Horan 3 dam respectively. The relative error shows a big difference from the actual data, which is a positive percentage for storing additional quantities of rainwater. That means the proposed program is better than the existing dam design, and thus the possibility of using this method to determine the optimal height of the proposed water harvesting sites.